(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article is devoted to the ways of expressing someone else’s speech in Uzbek and French, which is one of the important areas of the category of communicative purpose, and its simple technique, indirect speech. It focuses on the textual features of indirect speech (le disours indirect) and interrogative indirect speech. At the same time, the functional and semantic features of other types of speech in two languages are explained.